DOI: 10.25148/etd.fi12041115
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Young Adult Literature on Adolescents' Rape Myth Acceptance

Abstract: Whenever there was a question, Dr. Bliss had the correct answer. Dr. Laurie Shrage generously shared her knowledge of feminist theory and women's studies that were critical in completing this work. I would also like to thank Dr. Patricia Barbetta and Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
3

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 139 publications
(227 reference statements)
1
60
0
3
Order By: Relevance
“…Their discussion gave students who read the book a shared experience and an opportunity to discuss something that is typically a taboo subject for a classroom (Malo-Juvera, 2014). As evidenced by this study, reading Anderson's YA novel in class, and discussing it, had a more positive effect on the attitude of boys about whether girls were somehow complicit in the rape rather than victimized as compared to a class based on rape education with no fiction reading experience (Malo-Juvera, 2014). In other words, it seems that students who live these real-world experiences vicariously through reading YA novels are able to experience the cognitive and emotional growth associated with experiencing these problematic situations in a way that does not bring them physical harm.…”
Section: B E N E F I T S O F R E a D I N G Ya L I T E R A T U R E B Ementioning
confidence: 57%
See 1 more Smart Citation
“…Their discussion gave students who read the book a shared experience and an opportunity to discuss something that is typically a taboo subject for a classroom (Malo-Juvera, 2014). As evidenced by this study, reading Anderson's YA novel in class, and discussing it, had a more positive effect on the attitude of boys about whether girls were somehow complicit in the rape rather than victimized as compared to a class based on rape education with no fiction reading experience (Malo-Juvera, 2014). In other words, it seems that students who live these real-world experiences vicariously through reading YA novels are able to experience the cognitive and emotional growth associated with experiencing these problematic situations in a way that does not bring them physical harm.…”
Section: B E N E F I T S O F R E a D I N G Ya L I T E R A T U R E B Ementioning
confidence: 57%
“…This rigor takes the form of higher levels of text complexity, in addition to emphases on non-fiction or for YA to provide a solid venue for the types of skills teachers feel pressured to teach in their classrooms through movements like CCSS (Goering & Connors, 2014;J. Hayn et al, 2016) This deficit indicates that the impact of YA literature in the classroom is, indeed, a topic worthy of study (Beumer Johnson, 2011;Hayn et al, 2011;Malo-Juvera, 2014;Thompson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When utilizing the lens of sexual script theory, it is important to consider that peers are not the only source of social norms. Study findings highlight the fact that social norms are also influenced by as family, media, education, culture, and other social institutions (Bohner et al, 2010;Edwards & Vogel, 2015;Hust et al, 2014;Malo-Juvera, 2012). Sexual scripts are constructed based on influence and information from these multiple sources, including peers, as well.…”
Section: Measuring Sexual Orientationmentioning
confidence: 78%
“…Fay and Medway (2006), however, found that rape myth acceptance decreased in their study of students transitioning to high school with the use of a specific activity programme. More recently, Malo-juvera (2012) found that use of a young adult fiction book, Speak (Anderson, 1999), reduced rape myth acceptance in a high school group compared with a control group. In Scotland, sexual health and health promotion practitioners have been engaged in the development, delivery and evaluation of Rape Crisis Scotland's sexual violence prevention pack, a programme of prevention education delivered to young people in schools and youth groups (DMSS Research, 2014).…”
Section: Educationmentioning
confidence: 99%